1994
DOI: 10.1071/ea9940301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of level of concentrate fed once or twice daily on the milk production of cows grazing tropical pasture

Abstract: A group of 40 Holstein-Fresian cows grazing tropical pastures were supplemented from 14 days after calving with a grain-based concentrate containing 15% protein. Concentrate was given at nil, 2, 4, 6, and 8 kg/cow. day fed once daily after morning milking, and 4, 6, and 8 kg/cow.day in 2 equal feeds, after morning milking and before evening milking. The experimental period was 250 days for cows fed once daily and 150 days for those fed twice daily. Over 250 days of lactation, the milk yield of cows fed once da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…No previous research has evaluated the feeding of grain more than twice daily for cows on pasture, and no previous study has evaluated the amount of grain fed in this study. During early lactation, twice daily feeding versus once daily feeding of up to 8 kg/d of grain with tropical pastures resulted in increased milk yield (21). Neither our study nor the study of McLachlan et al ( 2 1 ) evaluated data on rumen fermentation to know whether it was altered by feeding frequency.…”
Section: Performance Of Cowsmentioning
confidence: 69%
“…No previous research has evaluated the feeding of grain more than twice daily for cows on pasture, and no previous study has evaluated the amount of grain fed in this study. During early lactation, twice daily feeding versus once daily feeding of up to 8 kg/d of grain with tropical pastures resulted in increased milk yield (21). Neither our study nor the study of McLachlan et al ( 2 1 ) evaluated data on rumen fermentation to know whether it was altered by feeding frequency.…”
Section: Performance Of Cowsmentioning
confidence: 69%
“…Thus, various reviews and studies (Davison et al, 1985;Kellaway and Porta, 1993;McLachlan et al, 1994;Robiana et al, 1998;Walker et al, 2001;Bargo et al, 2003) all suggest 4 to 5kg/cow/day as the maximum amount fed before a decline in response was observed. Walker et al (2001) compared their results with other studies and clearly showed an excellent milk response to the first 3-4kg concentrates fed and then a variable drop with some negative increments as concentrate fed increases.…”
Section: Discussionmentioning
confidence: 94%
“…There are numerous and complex interactions that influence the immediate marginal milk response to supplements. Factors such as season, the nutritive characteristics of pastures, pregrazing pasture mass and allowance of pasture on offer [4,15,18,37], amount of pasture consumed [4,18], amount and type of supplement consumed, nutritive characteristics of the supplement [4,5,18,23], amount of substitution [15,18] and animal and management factors, such as stage of lactation [5], body condition score [19], frequency of feeding [38] and genetic merit of cows [39], have all been shown to influence milk production when supplements are fed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, milk yields from animals lighter than 400 and heavier than 600 kg are largely untested, as are milk yields from cows beyond 270 days in milk. The influence of the genetic merit of cows [38] is also not captured in this model. Empirical models of this kind, developed on, and calibrated to, a wide diversity of experimental data collated from different locations in different decades, cannot detect and reliably represent the minutiae of biological processes.…”
Section: Discussionmentioning
confidence: 99%